Treatment of wastewater from kenaf water-retting process - Zainuddin, Zawani (2014)
Treatment wastewater from kenaf-retting process was implemented using three types of treatment process, namely coagulation, sequencing batch reactor (SBR) and adsorption process. Each of the tested process has advantages and disadvantages. Characteristic of wastewater was measured to determine presence of chemical composition. Concentration of chemical oxygen demand and colour were recorded in high concentration, which is more than 2000mg/L and 1000mg/L respectively. Most of parameters tested did not comply with the standard and regulation that regulated by Department of Environment (DOE) Malaysia. In coagulation process, five types of coagulants were selected based on its reputation achieved in previous research. There are ferric chloride, aluminium sulphate, ferric sulphate, Moringa oleifera and Jatropha curcas. Results obtained from the experiment have given satisfactory results; more than 90% of turbidity was removed from the wastewater by all coagulants tested. All coagulants tested except ferric sulphate required acidic condition to work at optimum condition. Nevertheless, for the removal of COD all coagulants showed an average performance. Then, the wastewater was tested with biological treatment, which activated sludge from nearby sewerage treatment plant used as source of bacteria. Diversity of microorganisms live in the sludge is a main criterion for the selection. Acclimatization process was implemented before biological treatment executed. Achromobacter, bacillus and acinetobacter were identified as dominant species lived in the wastewater. For biological treatment, sequencing batch reactor was selected to treat the wastewater. Two main parameters were tested; there are food-tomicroorganisms (F/M) ratio and hydraulic retention time (HRT). SBR shows the best condition at low F/M ratio, which is 0.25, and the lowest of COD concentration recorded was 163mg/L. whilst, for HRT, SBR showed the best efficiency at HRT 24 per cycle. At higher HRT, the performance of SBR becomes less efficient. The lowest COD value in the final effluent for HRT24 was recorded at 114mg/L. The last treatment process tested was adsorption process. Activated charcoal was selected as an adsorbent. The highest uptake rate in various initial pH was found at pH8, and the adsorption process efficiency in this experiment was pH dependent. The increasing amount of adsorbent dosage enhanced the COD removal rate, but not the sorption capacity. However, 1.0g of activated charcoal was selected as the best dosage when the cost of adsorbent and treatment take into consideration and the value of COD in the effluent was 339mg/L. In equilibrium studies, COD concentration had shown well agreed with the Redlich-Peterson with high correlation coefficient values compared to other models Combination of coagulation process with SBR and activated charcoal showed a good performance and high efficiency in removing total suspended solids, chemical oxygen demand and colour. Coagulation process is capable to remove COD and TSS averagely around 80% and 40% respectively. Through SBR-AC process, the value of COD become lower with the reduction recorded around 133mg/L only. Overall the integration process was the best treatment process compared to other three process.